Pengaruh Sastra dalam Pembentukan Karakter Bangsa dari Sudut Pandang Pendidikan Islam - Abidin, Zaenal (Maliki Interdisciplinary Journal, 2025)
This article discusses the influence of literature in shaping national character from the perspective of Islamic education. Literature, as a form of cultural expression, plays an important role in conveying moral and ethical values that can shape individual personality. In the context of Islamic education, literature not only serves as a tool for developing language and communication but also as a means to instill religious and social values. Through the analysis of various literary works, this article demonstrates how literary elements such as stories, poetry, and drama can contribute to character development, including honesty, responsibility, and empathy. These findings are expected to provide new insights for educators and policymakers in designing a more integrative curriculum that connects literature with character education within the Islamic context.